Providing Social Protection in the form of Pension Funds to the informal sector in Ghana: A Case Study of SSNIT Informal Sector Fund - Budu-Ainooson, Betty (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters in Business Administration,